Effects of Cannabis‐Delivered THC on mood and negative attentional bias in the context of positive vs. neutral Alternatives—a pilot study. (21st April 2022) - Gunn, Matthew P.; Rabinovich, Norka E.; Martens, Kris M.; Lindt, John D.; Gilbert, David G.
Abstract: Objective: To assess: (1) the acute effects of smoked marijuana (MJ) on negative attentional bias (NAB), (2) moderation of these effects by positive versus neutral alternatives, and (3) the associations of tetrahydrocannabinol (THC)‐induced changes in NAB with changes in affect. Methods: Fourteen MJ users (1–4 uses/wk) smoked a THC cigarette on 1 day and a placebo cigarette on the other counterbalanced day. After smoking, participants freely gazed back and forth at a series of two side‐by‐side pictures pairs presented for 3000 ms (one negative, while the other was either positive or neutral) while eye gaze was tracked. Results: The effects of THC relative to placebo varied across time such that THC increased NAB during the early temporal component of threatening picture viewing, 333–858 ms after dual‐picture onset, regardless of alternative picture valance. However, contrary to the attentional bias‐causes affect hypothesis, during the early viewing phase THC‐enhanced positive affect (PA) correlated positively with THC‐induced NAB. In contrast, during the late phase (891–3000 ms) THC‐enhanced PA did not correlate significantly with NAB, though THC‐induced negative affect (NA) change did correlate positively with THC‐induced change in NAB in the positive alternative condition. Conclusions: We replicated findings of others showing that THC can enhance NAB during the early stages of threatening picture viewing. We extended previous results by demonstrating the THC‐induced NAB is associated with increased PA during initial threat viewing, but with increased NA during later processing if positive alternatives are present.